Model Pembelajaran Sains Berbasis Al-Qur’an Pendekatan Project Base Learning (Studi Kasus Di SDS Al-Hikmah Mampang Jakarta Selatan) - EE. Junaedi Sastradiharj; Dahliah Dahliah (Journal on Education, 2023)
At the elementary school level, science learning outcomes contain the competencies and essential content which so far have focused more on aspects of cognitive competence. The competence of understanding and practicing religion is often forgotten. In fact, the goal of national education is to develop the potential of students to become human beings of faith and piety to God Almighty, have noble character, are healthy, knowledgeable, capable, creative, independent, and become citizens of a democratic and responsible state. To make human beings who believe and fear God Almighty, and have noble character, it is necessary to apply the Al-Qur'an based science learning model with the Project Base Learning approach, so that students can understand that all knowledge including science originates from Allah which is contained in the Al-Qur'an. The purpose of this study was to describe the steps for implementing the Qur'an based science learning model with the Project Base Learning approach at Al-Hikmah Mampang private elementary school, South Jakarta. The research method used a survey method with data collection techniques through interviews, observation of teachers and students of grades V as well as documentation studies. The results showed that the steps for implementing the Al-Quran-based science learning model with the Project Base Learning approach at Al-Hikmah Mampang Private Elementary School, South Jakarta started from the Learning Implementation Plan, namely the materials to be taught were given the spirituality of the contents of the Al-Quran, then explained in detail through Project Base Learning as well as deepening through learning evaluation.